Design of a multi-epitope vaccine against Haemophilus parasuis based on pan-genome and immunoinformatics approaches - Pang, Maonan; Tu, Teng; Wang, Yin; Zhang, Pengfei; Ren, Meishen; Yao, Xueping; Luo, Yan; Yang, Zexiao (Frontiers in Veterinary Science, 2022)
Abstract Background: Glässer’s disease, caused by Haemophilus parasuis (HPS), is responsible for economic losses in the pig industry worldwide. However, the existing commercial vaccines offer poor protection and there are significant barriers to the development of effective vaccines. (2) Methods: In the current study, we aimed to identify potential vaccine candidates and design a multi-epitope vaccine against HPS by performing pan-genomic analysis of 121 strains and using a reverse vaccinology approach. (3) Results: The designed vaccine constructs consist of predicted epitopes of B and T cells derived from the outer membrane proteins of the HPS core genome. The vaccine was found to be highly immunogenic, non-toxic, and non-allergenic as well as have stable physicochemical properties. It has a high binding affinity to Toll-like receptor 2. In addition, in silico immune simulation results showed that the vaccine elicited an effective immune response. Moreover, the mouse polyclonal antibody obtained by immunizing the vaccine protein can be combined with different serotypes and non-typable Haemophilus parasuis in vitro. (4) Conclusions: The overall results of the study suggest that the designed multi-epitope vaccine is a promising candidate for pan-prophylaxis against different strains of HPS.